Incidence of concussions and helmet use in equestrians - Glace, B. W.; Kremenic, I. J.; Hogan, D. E.; Kwiecien, S. Y. (Journal of Science and Medicine in Sport, 2023)
Objectives: Equestrians have a high risk of concussions per hospital records. However, most concussions occur in private settings where concussions are not tracked. We determined concussion incidence by self-report, expressed per 1000 h of exposure, and determined helmet usage and concussion knowledge. Design: Descriptive epidemiological study. Methods: Equestrians were recruited using a snowball method of sampling in which enrolled participants recruited more equestrians. Participants completed a survey of equestrian experience and history of concussion, symptoms and provided estimates of hours spent in various equestrian activities. From these data, incidences of concussions were calculated. In addition, they answered questions regarding helmet usage and willingness to take risks when concussed. Results: 210 participants (203 women) reported 27±14years of equine experience and 728 concussions, 3.47±5.34 per person (0-55). Incidence while riding was 0.19/1000 h which was greater than the incidence while driving (0.02/1000 h) or handling horses (0.03/1000 h). Riders were helmeted at the time of injury 85% of the time. While concussion knowledge was high, most reported willingness to risk permanent injury by continuing to work with horses while injured. Conclusions: To our knowledge this is the first study to document incidence of concussions in equestrians: incidence is higher while riding than during football or rugby training. Helmets were far more commonly worn at the time of concussion than reported in hospital data, suggesting that helmets effectively reduce concussions severe enough to warrant urgent medical care.